Anthropometric Wall Chart (AWC) Height for Screening Stunting Children - Sudja, Aryani; Moviana, Yenny; Purnawan, Asep Iwan; Mulyo, Gurid PE (International Journal of Psychosocial Rehabilitation, 2020)
Stunting is an indicator for a chronic undernourished or growth failure in the past. Stunting children may have a growth problem, low motoric skills, mental and intellectual disorders, low productivity and high risk to non-communicable diseases. It is important to detect stunting as earlier as possible. Early detection for stunting children’s tool easier and practicable is needed. AWC height for age is a bigger growth chart than the formerly known as Kartu Menuju Sehat (KMS). Its vertical axis shows children’s height in cm, and the horizontal axis shows children’s age 3 to 5 years. It is made from durable material and easy to hang on classroom walls. Its chart has three color ribbons, green, yellow and red. It screens stunting children by reading its colored ribbons. It is used by reading AWC color on children’s peak heads. Green color shows the child in good nutrition status. Yellow and red color show the child is stunting. There were 118 children aged 3-5 years from 4 kindergarten/Pre-School in Cimahi, Indonesia. There were 59 children for every gender group, with the same amount for each age groups. Their nutrition status was measured using AWC height for age and were compared to their nutrition status by height for age using WHO-NCHS 2005 reference. This study showed high Sensitivity and Specificity values (Se = 76.9%, Sp=96.2%, PPV =71.4% and NPV= 97.1%). AWC height chart can predict stunting children of 3-5 years old accurately.